2021
DOI: 10.1021/acs.langmuir.0c03418
|View full text |Cite
|
Sign up to set email alerts
|

New Water Oxidation Electrocatalyst Based on the Cobalt-Containing Polyoxometalate-Reduced Graphene Oxide Hybrid Nanomaterial

Abstract: A new hybrid nanomaterial based on the immobilization of cobalt-containing polyoxometalate (CoPOM) on the surface of reduced graphene oxide (rGO) was designed for an efficient electrocatalytic water splitting reaction. First, the surface of rGO was functionalized with aminopropylsilyl groups and protonated with hydrochloric acid to produce ammonium groups. Then, the electrostatic interaction of positively charged rGO-supported ammonium groups with anionic CoPOM produced a CoPOM−APTS−rGO hybrid nanomaterial. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Graphene oxide (GO) has attracted widespread attention in the past few years due to its unique physicochemical properties and the consequent possible applications in a wide range of fields. The abundant oxygen-containing groups, including carboxyl, hydroxyl, epoxy, and carbonyl, on the surface of GO endow it with great hydrophilicity to disperse well in water. Meanwhile, these oxygen-containing groups also endow it with high reactivity to be chemically modified. Chemical modification of GO could greatly enhance the target properties for specific purposes, such as catalytic performance, solubility in a less polar solvent, binding ability with other materials, and amphiphilicity regulation . In most of the cases, however, modification would inevitably affect the colloidal stability of the modified GO, which might affect its performance.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) has attracted widespread attention in the past few years due to its unique physicochemical properties and the consequent possible applications in a wide range of fields. The abundant oxygen-containing groups, including carboxyl, hydroxyl, epoxy, and carbonyl, on the surface of GO endow it with great hydrophilicity to disperse well in water. Meanwhile, these oxygen-containing groups also endow it with high reactivity to be chemically modified. Chemical modification of GO could greatly enhance the target properties for specific purposes, such as catalytic performance, solubility in a less polar solvent, binding ability with other materials, and amphiphilicity regulation . In most of the cases, however, modification would inevitably affect the colloidal stability of the modified GO, which might affect its performance.…”
Section: Introductionmentioning
confidence: 99%
“…The bands at 1635 and 1572 cm –1 are ascribed to the CO and CN stretching vibrations, respectively. The FTIR spectrum of clicked g-C 3 N 4 revealed two bands at 2918 and 850 cm –1 , which were related to the stretching vibrations of the CH 2 and C–S bonds of the immobilized cysteamine hydrochloride, respectively. , The bands at 953, 884, 750, and 451 cm –1 in the FTIR spectrum of CoW 12 /clicked g-C 3 N 4 are assigned to the WO t , W–O e –W, W–O c –W, and Co–O stretching vibrations, respectively . Such evidence verified the immobilization of CoW 12 species on the surface of clicked g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 52%
“…37,38 The bands at 953, 884, 750, and 451 cm −1 in the FTIR spectrum of CoW 12 /clicked g-C 3 N 4 are assigned to the W�O t , W−O e −W, W−O c −W, and Co−O stretching vibrations, respectively. 39 Such evidence verified the immobilization of CoW 12 species on the surface of clicked g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 61%
“…Recent studies have shown that the POM WOCs can be stabilized and activities enhanced by employing different supports such as metal‐organic frameworks (MOFs), [8a] zeolitic imidazole frameworks (ZIFs), [29] graphene oxide (GO) materials, [30] and carbon nanotubes (CNTs) [31] . In the future, this approach may be explored to check if 1–3 and similar POV‐based OER systems can serve as true electrocatalysts without degradation of the POV framework in alkaline media.…”
Section: Post‐catalytic Analysesmentioning
confidence: 99%